2023
DOI: 10.1073/pnas.2301775120
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds from Huashi Baidu decoction possess both antiviral and anti-inflammatory effects against COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is an ongoing global health concern, and effective antiviral reagents are urgently needed. Traditional Chinese medicine theory-driven natural drug research and development (TCMT-NDRD) is a feasible method to address this issue as the traditional Chinese medicine formulae have been shown effective in the treatment of COVID-19. Huashi Baidu decoction (Q-14) is a clinically approved formula for COVID-19 therapy with antiviral and anti-inflammatory effects. Here, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…It is widely accepted that antiviral TCMs can act by both preventing viral systemic spread through immuno-stimulation, and by enhancing the host's tolerance to virus infection through the suppression of overactivated inflammatory responses. 67,68 In addition, the diverse chemical structures within TCM constitutions may have the capacity to recognize at least one of the pivotal viral components, regardless of the virus species, thus directly blocking virus replication as a complementary mechanism of action. 68 These features enhance the efficacy of these antiviral TCMs in treating multiple virus infections, with only slight modifications of the recipe required to accommodate the differentiated clinical syndromes.…”
Section: Traditional Chinese Medicines Provide An Empirical Approach ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that antiviral TCMs can act by both preventing viral systemic spread through immuno-stimulation, and by enhancing the host's tolerance to virus infection through the suppression of overactivated inflammatory responses. 67,68 In addition, the diverse chemical structures within TCM constitutions may have the capacity to recognize at least one of the pivotal viral components, regardless of the virus species, thus directly blocking virus replication as a complementary mechanism of action. 68 These features enhance the efficacy of these antiviral TCMs in treating multiple virus infections, with only slight modifications of the recipe required to accommodate the differentiated clinical syndromes.…”
Section: Traditional Chinese Medicines Provide An Empirical Approach ...mentioning
confidence: 99%
“…67,68 In addition, the diverse chemical structures within TCM constitutions may have the capacity to recognize at least one of the pivotal viral components, regardless of the virus species, thus directly blocking virus replication as a complementary mechanism of action. 68 These features enhance the efficacy of these antiviral TCMs in treating multiple virus infections, with only slight modifications of the recipe required to accommodate the differentiated clinical syndromes.…”
Section: Traditional Chinese Medicines Provide An Empirical Approach ...mentioning
confidence: 99%
“…In addition, glycyrrhisoflavone and licoisoflavone A also displayed strong inhibitory activities against cAMP-specific 3′,5′-cyclic phosphodiesterase 4 (PDE4), and both compounds bind in the active site of PDE4 with similar interactions. [31] These results suggested that the synergistic effect of multicomponents and multitargets might be the reason for TCMFs to exert clinical efficacy.…”
Section: Fundamental Theory and Characteristics Of Traditional Chines...mentioning
confidence: 99%
“…[75–77] These effects are probably through the mechanism of inhibiting the SARS-COV-2 replication and reducing proinflammatory cytokines. [31,78,79] The 12-month results of the largest longitudinal cohort study of COVID-19 hospitalized adult survivors to date showed that many COVID-19 patients will fully recover after more than 1 year. [80]…”
Section: Does It Work?mentioning
confidence: 99%
“…Among these, echinatin and quercetin were identified as inhibitors of main protease (3CL pro ), while glycyrrhisoflavone and licoisoflavone A were found to inhibit the RNA-dependent RNA polymerase (RdRp). Additionally, three anti-inflammatory components, namely licochalcone B, echinatin, and glycyrrhisoflavone, were identified in a SARS-CoV-2-infected inflammatory cell model [100] . From network pharmacological analysis, eight common targets, including FYN, SFTPD, P53, retinol-binding protein 4 (RBP4), IL1RN, TTR, serine/arginine protein kinase1 (SRPK1), and AKT1, were identified by overlapping the targets of HSBD and COVID-19.…”
Section: Mechanisms Through Which Tmtfs Regulate Immune and Inflammat...mentioning
confidence: 99%